2016
DOI: 10.2497/jjspm.63.451
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Minor Boron Addition on the Fatigue Strength and High Temperature Properties of Injection Molded Ti-6Al-4V Compacts

Abstract: Ti-6Al-4V alloy has attracted a lot of attention from the automotive and aerospace industries because of their outstanding specific strength and corrosion resistance. On the other hand, Ti-6Al-4V alloy has normally poor workability because of the low thermal conductivity and the low elastic modulus. Metal injection molding (MIM) process is expected to manufacture a complex part with near net shape and reduce the manufacturing cost. However, Ti-6Al-4V alloy compacts by MIM process had a problem of low fatigue s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…13 Relationships between ratio of estimated value of maximum pore diameter to mean grain diameter and ratio of fatigue strength based on HIP treated compacts. Data of boron added compacts and Ti64-fine powder compacts are references (Choe et al, 2016) .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…13 Relationships between ratio of estimated value of maximum pore diameter to mean grain diameter and ratio of fatigue strength based on HIP treated compacts. Data of boron added compacts and Ti64-fine powder compacts are references (Choe et al, 2016) .…”
Section: Resultsmentioning
confidence: 99%
“…Several papers have reported that the fatigue strength of the Ti-6Al-4V alloy is proportional to the reciprocal of the square root of the grain size (Choe et al, 2016) (Okazaki et al, 1992) . This means that the fatigue strength and the fatigue crack initiation stress are equal.…”
Section: Effect Of Grain Diameter and Pore Diameter On The Fatigue Stmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, research has demonstrated that it is possible for the MIM process to manufacture Ti64 components with superior mechanical properties close to the ASTM standard range [5,43,51,100,101] especially by small addition of other elements such as B [43,45], C [71], Gd [58] and TiC [81]. However, most research work on MIM of Ti64 alloy has been specifically designed for biomedical applications [43,83,102] rather than other applications such as aerospace. Table 1, summarizes powder and binder characteristics as well as properties obtained from some selected research on MIM of Ti64 alloys.…”
Section: Figure 6 Microstructure Of Mim Proceed Cp-ti Samples From Amentioning
confidence: 99%
“…The most successful process may be a small addition of grain refining agents such as boron, LaB 6 and TiC to the feedstock [43,45,[81][82][83]. Post sintering heat treatments may also improve the ductility and strength of MIM components through their modification of microstructure.…”
Section: Figure 3 Dependence Of Yield Strength On Inverse Square Roomentioning
confidence: 99%